Consumer acceptance of Islamic home financing - Hanudin, Amin; Abdul Rahman, Abdul Rahim; Abdul Razak, Dzuljastri (Emerald Publishing Group, 2014)
This study aims to examine the factors influencing the consumer acceptance on Islamic home financing products amongst clients of Islamic banks. For the purpose, the study extends the theory of planned behaviour (TPB)in explaining the Islamic home financing adoption along. Further, the study also intends to analyze the effects of "Islamicity of products" and seven demographic factors on the consumer acceptance of Islamic home financing products.